The Role of Massive Ice and Exposed Headwall Properties on Retrogressive Thaw Slump Activity. Issue 11 (26th November 2022) - Hayes, Samuel; Lim, Michael; Whalen, Dustin; Mann, Paul J.; Fraser, Paul; Penlington, Roger; Martin, James
Abstract: Retrogressive Thaw Slumps (RTSs), a highly dynamic form of mass wasting, are accelerating geomorphic change across ice‐cored permafrost terrain, yet the main controls on their activity are poorly constrained. Questions over the spatial variability of environmentally sensitive massive ice bodies and a paucity of high‐spatial and temporal resolution topographic data have limited our ability to project their development and wider impacts. This research addresses these key problems by investigating RTS processes on Peninsula Point—a well‐studied site for intra‐sedimental massive ice in the Western Canadian Arctic. Utilizing high‐resolution topographic data from drone surveys in 2016, 2017 and 2018 we (a) measure the temporal and spatial variations in headwall properties and retreat rates, (b) determine the spatial pattern of subsurface layering using passive seismic monitoring and (c) combine these to analyze and contextualize the factors controlling headwall retreat (HWR) rates. We find that headwall properties, namely massive ice and overburden thickness, are significant controls over rates of HWR. Where persistent massive ice exposures are present inland of the headwall, regardless of thickness, and overburden thickness remains <4 m, HWR is typically more than double that of other headwalls. Furthermore, a 3D site model was created by combining photogrammetric and passive seismic data, highlighting internal layering variability and demonstrating the limitations of extrapolations of internal layering based on headwall exposures. These results provide fresh insights into the in situ controls on HWR rates and new approaches to understanding their variability. Plain Language Summary: Retrogressive thaw slumps (thaw slumps) are a form of landslide that occurs when thick layers of ice under the ground are exposed and thaw, creating muddy flows that can grow to cover thousands of m 2 in just a few years. These processes are occurring more frequently in the western Canadian Arctic during the last two decades, becoming one of the primary causes of landscape change. This research examines how variation in the ice and overlying soil thickness of the thaw slump headwalls (a prominent, near vertical cliff at the back of a thaw slump), affects their rate of growth. We find that a persistent layer of ice, and a thin soil overburden, tends to promote headwall retreat rates much faster than otherwise. We also show how simple, cost‐effective and quick measurements can be used to map the ice layers and show how they vary inland. This research suggests that detailed knowledge of how the internal ice and overburden layering varies is critical to understanding how thaw slumps evolve and to predict their development. Key Points: Active headwall properties strongly influence rates of headwall retreat Passive seismic monitoring is an effective tool for detecting and mapping massive ice surface variability Subsurface massive ice and overburden thickness display variations not predicted from extrapolations of headwall exposures